ANALISIS RESIDU PESTISIDA PADA JERUK MANIS DI KECAMATAN DAU, MALANG - Astri Sumiati; Reza Prakoso Dwi Julianto (Universitas Tribhuwana Tunggadewi, 2017)
Citrus is one type of fruit that is highly favored by the people. Citrus plants are vulnerable to pests and plant diseases that intensive use of pesticides in the field can not be avoided. Citrus fruits commonly consumed in the form of raw materials that need to be considered food quality and safety of citrus fruits to public health. This study aims to identify and analyze pesticide residues in citrus fruits in the district of Dau, Malang (a case study in the Village Tegalwaru subdistrict Dau, Malang) as one of the centers of citrus production in East Java with the use of pesticides are quite diverse. This research is a survey and observational with cross sectional approach. Data use of pesticides by farmers was measured by a survey conducted for the farmers and merchants. The sample was 3 kg of oranges produced by three farmers and 3 kg of oranges produced by 3 merchants Village Tegalwaru District of Dau, Malang where interviews illustrate the differences in the type and frequency of the use of pesticides during the growing season oranges, which is a high level (sample A ), medium (sample B) and low (sample C). The measurement results residues acephate, carbofuran, carbosulfan, diazinon, dimethomorp, fenobucarb, profenofos, pyrethrin everything is still below the Limit of Detection (LOD) testing in the laboratory PT. Angler Biochem Lab. In profenofos residue tests on samples found to be higher farmer is 0.108 ppm compared with a sample of traders is 0,050 ppm. The conclusions of this study are bauh oranges produced by farmers in the sub-district Tegalwaru Dau, Malang get evidence that pesticide residues are still below the prescribed MRL.